Experimental prototype for PWM – Based Sliding Mode Boost Converter - Abdulhalem, R. A.; Hairik, Haroutuon A.; Kadhem, Asmaa J. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
The paper dells with a modified experimental prototype for pulse-width modulation (PWM) sliding mode control (SMC) applied to a DC-to-DC-boost converter operated in continuous conduction mode (CCM). Experimental results show that the proposed control schme provides good voltage regulation and is suitable for common DC-to-DC conversion purposes. The prototype and its implementation are given in detail. The static and dynamic performances of the The static and dynamic performances of the experimental system are recorded. Experimental results show that the proposed control scheme provides good voltage regulation and is suitable for common DC-to-DC conversion purposes.